Percutaneous management of coronary sinus atrial septal defect: two cases representing the spectrum for device closure and a review of the literature. (25th March 2014) - Sandeep, Nefthi; Slack, Michael C.
Abstract Coronary sinus atrial septal defects are the rarest defects of the atrial septum comprising <1% of the five different types of atrial septal defects. Despite the widespread adoption of percutaneous device closure of secundum atrial septal defects, the published experience with percutaneous device closure of coronary sinus atrial septal defects is limited to only a few isolated case reports because of uncertainty regarding safety and efficacy. Open-heart surgical repair remains the treatment of choice for coronary sinus atrial septal defects, although this may not be the only treatment option in selected cases. Herein we describe our own experience with two patients with different clinical presentations and our method of successful percutaneous coronary sinus atrial septal defect closure in each. We then present a review of the anatomic spectrum of coronary sinus atrial septal defects along with a review of contemporary surgical and percutaneous device treatment.